2019
DOI: 10.1002/jor.24480
|View full text |Cite
|
Sign up to set email alerts
|

Analgesic Effect of Duloxetine on an Animal Model of Monosodium Iodoacetate‐Induced Hip Osteoarthritis

Abstract: We investigated the efficacy of duloxetine on hyperalgesia, histopathological and radiographic findings, pain-related sensory innervation of dorsal-root ganglia (DRG), and spinal changes in a rat model of induced hip osteoarthritis (OA). The right hip joints of male Sprague-Dawley rats (n = 6 rats/group) in the Sham group were injected with 25 μl of sterile saline and 25 μl of sterile saline with 2 mg of monosodium iodoacetate (MIA) were injected to the MIA + Vehicle and MIA + Duloxetine groups. We injected du… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
10
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 7 publications
(12 citation statements)
references
References 52 publications
(85 reference statements)
2
10
0
Order By: Relevance
“…32,33 Recent studies reported that the rat hip OA model induced by 2.0 mg of MIA exhibits peripheral inflammation, local nerve damage, and central sensitization, thus leading to chronic pain. 13,34,35 Regarding tramadol administration in the MIA model, Rachel et al 14 reported that tramadol administration improved mechanical hypersensitivity in the knee of MIA-induced OA model animals. Ishikawa et al 17 similarly reported that tramadol administration improved the gait paradigm in a rat knee OA model induced by MIA.…”
Section: Histopathological Findingsmentioning
confidence: 99%
See 1 more Smart Citation
“…32,33 Recent studies reported that the rat hip OA model induced by 2.0 mg of MIA exhibits peripheral inflammation, local nerve damage, and central sensitization, thus leading to chronic pain. 13,34,35 Regarding tramadol administration in the MIA model, Rachel et al 14 reported that tramadol administration improved mechanical hypersensitivity in the knee of MIA-induced OA model animals. Ishikawa et al 17 similarly reported that tramadol administration improved the gait paradigm in a rat knee OA model induced by MIA.…”
Section: Histopathological Findingsmentioning
confidence: 99%
“…It has also been reported that duloxetine exerts a pain-relieving effect on neuropathic pain in this animal model. 13 Tramadol is a weak opioid that acts on µ-opioid receptors, with a lower affinity for the receptor than morphine. 14 Tramadol is widely recognized and used for relieving pain in OA.…”
mentioning
confidence: 99%
“…The histological OARSI scores were 22.7. Thus, the radiographic and histological outcomes were similar [ 11 ]. Our results are consistent with these.…”
Section: Discussionmentioning
confidence: 99%
“…They reported that, in rats with hip OA induced by 0.5 mg of MIA, OARSI scores were approximately 10 at 4 weeks after induction [ 27 ]. By contrast, another study reported that OARSI scores were almost at maximum 4 weeks after administration of 2 mg of MIA into the hip joint [ 11 ]. These results validate our findings, i.e., more than 2 mg of MIA provoked end-stage OA at 8 weeks after injection.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation